Glasses for People with Visual and Hearing Impairment - Sarma R, Lokesh; Krishna C T, Akshay; Sumithra, KC.; Brightex, J.; Kumar B, Suresh (Center of Excellent (Pusat Unggulan Iptek), 2026)
Background: Individuals with both visual and hearing impairments face significant mobility challenges. Traditional aids such as canes and guide dogs provide limited support, necessitating innovative assistive technologies to enhance independent navigation. Purpose: This study aims to develop and evaluate smart glasses integrating ultrasonic sensors and haptic feedback to assist individuals with dual sensory impairments in detecting obstacles and improving mobility. Methods: A single case study assessed the effectiveness of the glasses. The prototype employs ultrasonic sensors for obstacle detection and a microcontroller to process data, triggering vibrations for user alerts. Testing in controlled and real-world environments evaluated detection accuracy, usability, and user experience. Results: The glasses effectively detected obstacles and provided real-time haptic feedback, enhancing spatial awareness. Participants reported improved confidence and ease of navigation. The lightweight, ergonomic design ensured comfort and practicality. Conclusion: These smart glasses present a promising assistive technology for individuals with visual and hearing impairments. By providing real-time haptic feedback, they enhance mobility and independence, demonstrating the potential of wearable technology in rehabilitation and assistive care.